Law on Amending and Supplementing to a number of articles of the Penal Code - The National Assembly (1997)
This Law amends and supplements a number of articles of the Penal Code which was adopted on June 27, 1985, amended and supplemented on December 28, 1989, August 12, 1991 and December 22, 1992 by the National Assembly of the Socialist Republic of Vietnam